Analiza interartystyczna ekfraz: Lekcja muzyki Vermeera w interpretacji Adama Zagajewskiego i Joanny Pollakówny - Słodczyk, Rozalia (Slavia Occidentalis, 2017)
The article focuses on the issue of describing a work of art in an essay. The paper presents ekphrasis and underlines the efficiency of an inter-artistic analysis in studying the phenomenon of ekphrasis. An interpretation of fragments of Zagajewski’s and Pollakówna’s essays starts with presenting two works of art, The Music Lesson and Girl Interrupted at Her Music by Vermeer, from the perspective of art history. It is followed by a discussion of the verbal accounts of the paintings by Zagajewski and Pollakówna. Their contents and poetics are examined with special emphasis placed on the nature of the suggested description as it may focus on either the subject or the viewer, the representation itself or its connotations. Accordingly, it is suggested that the corresponding modes of ekphrasis should be labelled ‘denotational’ and ‘connotational’. In his description, Zagajewski resorts to an example of connotational ekphrasis whereas Pollakówna’s textual relation is a fine example of mixing the denotational and connotational facets of ekphrasis. The article presents specifi realizations of ekphrasis and the characteristic modes of perceiving works of art and describing them. It also shows how the observer’s subjective perspective and idiomatic style of expression manifest themselves.